Establishment of the World Health Organization 2nd International Standard for Factor XI, Plasma, Human - Wilmot, Helen; Hockley, Jason; Rigsby, Peter; Gray, Elaine (Frontiers in Medicine, 2017)
The 1st International Standard (IS) for Blood Coagulation Factor XI, Plasma, has been successfully used for potency labelling of factor XI (FXI) therapeutics and for diagnosis of FXI deficiency in patients. With stocks of the 1st IS near depletion, a replacement is required. In addition to the functional activity value, assignment of an antigen value to the 2nd IS would allow harmonization of antigen assay methods and differentiation of patients who have low functional activity but normal antigen FXI levels from patients who have both low functional and antigen FXI levels. The aims of this study were therefore to assign FXI functional activity to the 2nd IS for Factor XI, Plasma, and to additionally assign a new analyte, FXI antigen, to the same International Standard. The candidate material was prepared from double-spun, virology negative, normal plasma which was pooled and filled into siliconized glass ampoules and subsequently freeze-dried. Assignment of the functional activity (FXI:C) value in International Units (IU) was performed by one-stage clotting assay by 29 laboratories, relative to the 1st IS. The overall geometric mean was 0.71 IU/ampoule with extremely low inter-laboratory variability (expressed as geometric coefficient of variation) of 1.8%. The antigen value assignment was performed by 11 laboratories and was calculated relative to normal plasma pools, as is customary with new coagulation factor analytes. The amount of antigen present in 1 ml of normal plasma was taken to be 1 unit. The overall geometric mean for the antigen assays was 0.78 IU/ampoule with an inter-laboratory variation of 10%. The candidate (15/180) was established by the World Health Organization (WHO) Expert Committee on Biological Standardization (ECBS) in 2016 as the WHO 2nd IS for Blood Coagulation Factor XI, Plasma, with a functional activity value (FXI:C) of 0.71 IU/ampoule and an antigen value (FXI:Ag) of 0.78 IU/ampoule.